UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN TOMAT BUAH (Lycopersicon esculentum Mill, var. pyriforme Alef) DAN DAUN TOMAT SAYUR (Lycopersicon esculentum Mill, var. commune Bailey) DENGAN METODE DPPH (1,1-Diphenyl-2-Picryl Hydrazil) - Mamat Pratama; Muzakkir Baits; Rizky Nurul Yaqin (Jurnal Fitofarmaka Indonesia, 2015)
Antioxidant are chemical compounds that can donate one or more electrons to free radicals, so that the free radical reaction is inhibited. Generally, the compounds that have potential as an antioxidant are flavonoids, phenolics and alkaloids. Leaves of tomato (Lycopersicon esculentum Mill.) are plants that contain alkaloid. This study aims to determine the antioxidant activity of the ethanol extract of leaves of fruit tomato (Lycopersicon esculentum Mill, var. pyriforme Alef.) and leaves of vegetable tomato (Lycopersicon esculentum Mill, var. commune Bailey.) with DPPH method (1,1-Diphenyl-2-Picryl Hydrazil). Ethanol extract is obtained by extracting the leaves of friut tomato powder (Lycopersicon esculentum Mill, var. pyriforme Alef.) and the leaves of vegetable tomato (Lycopersicon esculentum Mill, var. commune Bailey.) with maceration. Antioxidant activity was measured using a UV-Vis spectrophotometer with maximum absorption wavelength is 514 nm. Readable absorbance is used to calculate % inhibition and IC50. The results showed that the samples of the leaves of fruit tomato (Lycopersicon esculentum Mill, var. pyriforme Alef.) and leaves of vegetable tomato (Lycopersicon esculentum Mill, var. commune Bailey.) have antioxidant activity with IC50 values of each of 279.482 µg/mL and 280.190 µg/mL. This shows the ethanol extract of leaves of fruit tomato (Lycopersicon esculentum Mill, var. pyriforme Alef.) and leaves of vegetable tomato (Lycopersicon esculentum Mill, var. commune Bailey.) has a very weak activity as an antioxidant.